ENT600: MyTurn apps of Piratas Barbershop / Anis Suhaila Razman … [et al.] - Mat Din, Mardhiah; Tawfik Teow, Muhammad Aidil; Sabri, Nor Farahin (2018)
This study aims to help organizations or small businesses to organize their sales and high customer demands that have been one of the organizations goals. This will help the organization and small businesses to continuously grow and improve their services. The customers often complain that the waiting time is often too long and the system of taking turns with writing name is an old-school method that they do not prefer.